2004
DOI: 10.1002/art.20218
|View full text |Cite
|
Sign up to set email alerts
|

Expression of interleukin‐21 receptor, but not interleukin‐21, in synovial fibroblasts and synovial macrophages of patients with rheumatoid arthritis

Abstract: Our data demonstrate that IL-21R is expressed in RA synovium by RASFs and synovial macrophages. IL-21R is associated with the activated phenotype of RASFs independently of the major proinflammatory cytokines IL-1beta and TNFalpha, but correlates negatively with the destruction of articular cartilage and bone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
142
2
2

Year Published

2005
2005
2014
2014

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 162 publications
(153 citation statements)
references
References 16 publications
(25 reference statements)
7
142
2
2
Order By: Relevance
“…Therefore, we used an ELISA to measure IL-21 production in cultured FLS. However, similar to what was observed in a previous study (22), IL-21 was not expressed by cultured RA FLS (data not shown). We also examined serum IL-21 concentrations, which were shown to be significantly higher in patients with RA (n ϭ 30) than in patients with OA (n ϭ 29) (mean Ϯ SD 332.1 Ϯ 121 pg/ml and 131.5 Ϯ 56 pg/ml, respectively; P Ͻ 0.01).…”
supporting
confidence: 91%
“…Therefore, we used an ELISA to measure IL-21 production in cultured FLS. However, similar to what was observed in a previous study (22), IL-21 was not expressed by cultured RA FLS (data not shown). We also examined serum IL-21 concentrations, which were shown to be significantly higher in patients with RA (n ϭ 30) than in patients with OA (n ϭ 29) (mean Ϯ SD 332.1 Ϯ 121 pg/ml and 131.5 Ϯ 56 pg/ml, respectively; P Ͻ 0.01).…”
supporting
confidence: 91%
“…Indeed, we recently showed that IL-21 is produced in excess in the inflamed gut of patients with inflammatory bowel diseases, such as Crohn's disease and ulcerative colitis, and that IL-21 helps sustain the ongoing Th1 cell response in the gut of patients with Crohn's disease (3). Moreover, enhanced expression of IL-21 and IL-21R has been described in patients with systemic sclerosis (4), and up-regulation of IL-21R also occurs in synovial macrophages and fibroblasts of patients with rheumatoid arthritis (24). Studies in experimental models of autoimmune diseases have also shown that administration of IL-21 into mice enhances the recruitment of leukocytes into inflamed tissues and increases the severity of the inflammation (25).…”
Section: Discussionmentioning
confidence: 99%
“…Limitations of in vitro migration assays include evaluating the role of a particular chemokine as it relates to other chemokines and chemokine receptors, and ranking the importance of chemokines and chemokine receptors in a particular disease. Indeed, many investigators have used a similar SCID mouse chimera to study the effects of gene therapy and RA ST fibroblast infiltration in vivo (41)(42)(43). Therefore, to evaluate the proinflammatory function of chemokines in RA, we developed an in vivo cell migration assay to determine the relative importance of chemokines and their respective cellular receptors in a human RA ST-SCID mouse chimera.…”
Section: Discussionmentioning
confidence: 99%